Dual Trigger for Final Follicular Maturation Improves Cumulative Live-Birth Rate in Ovarian Stimulation for Freeze-All In Vitro Fertilization/Intracytoplasmic Sperm Injection Cycles - Zhu, Haiyan; Zhao, Chenqiong; Pan, Yibin; Zhou, Hanjing; Jin, Xiaoying; Xu, Wen; Zhang, Songying (Frontiers in Endocrinology, 2021)
Research Question: Does dual trigger in freeze-all in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles improve the cumulative live-birth outcome compared with human chorionic gonadotropin (hCG) trigger? Design: A 6-years population-based retrospective cohort analysis using individual patient data. A total of 4438 women were analyzed from their single ovarian stimulation cycle until they had a live birth or had used all their embryos. Result(s): A total of 4438 IVF/ICSI cycles were analyzed, including 1445 cycles with single hCG trigger and 2993 cycles with dual trigger. The cumulative biochemical pregnancy rate (60.8% vs. 68.1%, P<0.001; odds ratio (OR): 0.727; 95% confidence interval (CI): 0.638–0.828), cumulative clinical pregnancy rate (52.9% vs. 58.5%, P<0.001; OR: 0.796; 95%CI: 0.701–0.903), and CLBR (44.3% vs. 50.5%, P<0.001; OR: 0.781; 95%CI: 0.688–10.886) were all significantly lower in the hCG-trigger group compared with the dual-trigger group. The clinical pregnancy rate (48.2% vs. 58.2%, P=0.002; OR: 0.829; 95%CI: 0.737–0.934), embryo implantation rate (34.4% vs. 38.9%, P<0.001; OR: 0.823; 95%CI: 0.750–0.903), and live-birth rate (26.6% vs. 31.7%, P<0.001; OR: 0.783; 95%CI: 0.709–0.864) were also significantly lower in the hCG-trigger group compared with the dual-trigger group. After controlling for all potential confounding variables, the trigger method was identified as an independent factor affecting the CLBR. The OR and 95%CI for hCG trigger were 0.839 and 0.711–0.990 (P=0.037). Conclusion(s): Dual trigger for final follicular maturation improves the cumulative pregnancy and live-birth rates compared with hCG trigger in freeze-all IVF/ICSI cycles.